Apuntes sobre los efectos de los incendios forestales y restauración ambiental de área quemadas. Estado de la cuestión y principios generales - Pérez-Cabello, Fernando; Echeverría, Maria Teresa; de la Riva, Juan; Ibarra, Paloma (Geographicalia, 2014)
The incidence of wildfires on Mediterranean ecosystems -as aresult of the increase of the number of fires and the burned area- has become one of the most important environmental problems in the recent decades. Fire affects soil characteristics, vegetation, wildlife, morphogenetic processes, landscapes and human activities. Once the disturbance occurred, the burned areas require restoration strategies supported by an integrated analysis of the territory in terms of physical and human aspects, and especially in the interaction of them. This paper presents a brief state of the art and reviews some general principles concerning integral restoration of burned areas for which there is consensus in the literature.
Keywords: Wildland fires; environmental effects; analysis of the territory; integral restoration plan.